A crisis in the shadows: public health outcomes and barriers to care for children of North Korean defectors in China - Jeong, Ji-Ung (Frontiers in Public Health, 2025)
BackgroundChildren born to North Korean defectors in China are effectively stateless and legally invisible, creating severe structural barriers to healthcare. This policy-driven public health crisis, marked by poor physical and mental health outcomes, remains critically underexamined from a healthcare perspective. This study aims to analyze the policy discourse to identify these structural barriers and understand how the health of this vulnerable pediatric population is framed and contested over time.MethodsA longitudinal qualitative content analysis was conducted on official documents from the UN Committee on the Rights of the Child (CRC) treaty-reporting cycles. The analysis covers the period from 2005 to 2022, systematically comparing the evolving positions of the Chinese government, the CRC, and civil society organizations on health-related issues.ResultsThe analysis reveals a persistent discursive stalemate. China consistently employs a strategy of deflection and denial, framing North Koreans as “illegal economic migrants” and a security threat, a position that has not changed over the 17-year period. In contrast, the CRC’s critique evolved from general concerns about “irreparable harm” to a specific focus on the de facto statelessness and denial of legal identity as the primary barrier to pediatric care for these children.ConclusionState policies that deny legal identity are the primary structural determinants of this public health crisis, systematically producing poor health outcomes. The analysis confirms that while the UN reporting system is limited in its enforcement capacity, it is crucial for documenting these violations. To mitigate harm, future health policy and advocacy should focus on the key recommendation of decoupling access to essential pediatric services from a child’s legal or household registration status.